Diet, oxidative stress and MAFLD: a mini review - Hu, Zenan; Yue, Hanxun; Jiang, Na; Qiao, Liang (Frontiers in Nutrition, 2025)
Globally, metabolic dysfunction-associated fatty liver disease (MAFLD), also known as non-alcoholic fatty liver disease (NAFLD) or metabolic dysfunction-associated steatotic liver disease (MASLD), is a common chronic liver disease. The progression of MAFLD leads to a vicious cycle in which oxidative stress results from the disease that is augmenting de-novo lipid levels and increases steatosis. Most non-enzymatic antioxidants are present in food. Therefore, the present review summarizes the findings of studies on food-derived antioxidants and presents an oxidative stress-related regulatory network in MAFLD, offering new ideas for MAFLD prevention and treatment.